Simulation Based Method for Design and Application of Digital Control System - Peter Drgona; Anna Prikopova; Michal Frivaldsky; Martin Priecinsky (Communications - Scientific letters of the University of Zilina, 2011)
With increasing number of microprocessors and DSP use as a control system in power semiconductor converters, the new approaches for design of digital control system must be implemented. Designing a digital control system requires use of control to output transfer function. For new, frequency controlled resonant converters, like LLC converter, standard averaging methods cannot be applied for revealing the transfer function. Instead of that, new simulation based, numerical methods must be employed.